Exploring Shree Mahalaxmi Plant Nursery: A Great Place for Users to Order Plants and Gardening Activities - Karande, Shital; Zambare, Shweta; Salunkhe, Shivanjali; Arkile, Sanika; Chavan, Vidya (International Journal of Computer Sciences and Engineering, 2024)
The Shree Mahalaxmi Plant Nursery Website is designed to facilitate the efficient management of plant nurseries through an accessible digital platform. The primary users of this system include nursery managers, staff members, and customers. The system’s main objective is to streamline the management of plant inventory, monitor plant health and growth, and enhance communication between the nursery and its clientele. By incorporating a robust online messaging system, the platform ensures that updates on plant availability, care instructions, and other relevant information are communicated quickly and accurately, minimizing the risk of errors and data mishandling. To develop this system, a comprehensive investigation was carried out to identify prevalent issues in traditional plant nursery operations and devise effective digital solutions. The platform features an intuitive dashboard for easy navigation and access to vital information, along with analytics tools for tracking sales trends and customer preferences. Additionally, it supports seamless integration with e-commerce functionalities, enabling nurseries to expand their reach and improve customer engagement.